High Development, Effective Policies, and Human Capital in the face of an intricate International System: A study of Costa Rica’s Path from 1950 to 2000. - Chávez Yumiceba, Roberto Alejandro; Umaña Vargas, Jorge (IJRDO - Journal of Social Science and Humanities Research, 2016)
Costa Rica is catalogued as a middle income country. With a territory of 51,100 km2 and a population of about 4.5 million, its impressive social development indexes shed light on the fact that in many aspects, the nation statistically resembles a high income country. These figures are the result of public policies and governmental decisions, which this paper reviews, while seeking to explain the successful development case of this Central American nation